2019
DOI: 10.1038/s41598-019-40708-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on thyroid gland: dose-related effect of urinary cotinine levels on thyroid function and thyroid autoimmunity

Abstract: Cigarette smoking is believed to affect thyroid function and autoimmune thyroid disease. However, there is little information to analyze their association using objective biomarkers. The aim of this study was to investigate the dose-related effect of smoking on thyroid hormones and thyroid peroxidase antibody (TPO Ab) using urinary cotinine levels and a population-based cohort. The present study used the thyroid hormone and urinary cotinine dataset from sixth Korean National Health and Nutrition Examination Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
4
29
0
2
Order By: Relevance
“…These findings would be consistent with an effect of smoking on thyroid-directed autoimmunity as for example widely appreciated in Graves disease and thyroidassociated ophthalmopathy [9,10]. In comparison, previous cohort studies have variably reported increased [15] and decreased [30,31] anti-TPO positivity in relation to Smoking status is categorized as never (reference category); former and current, which is divided in <20 and ≥20 cigarettes per day. β: standardized regression coefficients F female, FT4 free thyroxine, FT3 free triiodothyronine, M male, TSH thyroid stimulating hormone.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings would be consistent with an effect of smoking on thyroid-directed autoimmunity as for example widely appreciated in Graves disease and thyroidassociated ophthalmopathy [9,10]. In comparison, previous cohort studies have variably reported increased [15] and decreased [30,31] anti-TPO positivity in relation to Smoking status is categorized as never (reference category); former and current, which is divided in <20 and ≥20 cigarettes per day. β: standardized regression coefficients F female, FT4 free thyroxine, FT3 free triiodothyronine, M male, TSH thyroid stimulating hormone.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, with some exceptions, evidence has accumulated since that cigarette smoking is associated lower TSH and higher FT4 levels, whereas T3 and FT3 were also found to be higher or unaltered [9,10,12,13]. In addition, using serum or urinary cotinine as a measure of nicotine exposure it was found that smoke exposure is associated with lower TSH levels [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the three substances (cocaine, nicotine, and opioids) that showed an interactive effect with rs8052287 on SI have been investigated previously with respect to thyroid homeostasis. Cigarette smoking appears to affect thyroid function with a dose-related effect linking cotinine levels to thyroid function and thyroid autoimmunity 46 . Cocaine abuse has been linked to the disruptions in the hypothalamic-pituitary-thyroid axis 47 and cocaine use has been suggested as a possible trigger for thyroid storm 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis from the Korean National Health and Examination Survey evaluated associations between urinary cotinine (a metabolite of nicotine used routinely to assess exposure to tobacco) and thyroid function [60]. There was no significant association between FT4 and urinary cotinine, but TSH was correlated negatively with the cotinine levels in men and women, and levels of anti-TPO antibodies correlated positively with cotinine in men.…”
Section: Serum Tsh As the Principal Diagnostic Marker Of Systemic mentioning
confidence: 99%